2023
DOI: 10.1002/ijgo.15220
|View full text |Cite
|
Sign up to set email alerts
|

Modified one‐step conservative uterine surgery (MOSCUS) versus cesarean hysterectomy in the management of placenta accreta spectrum: A single‐center retrospective analysis based on 619 Vietnamese pregnant women

Anh Dinh Bao Vuong,
Thanh Hai Pham,
Xuan Trang Thi Pham
et al.

Abstract: ObjectivesTo compare maternal outcome measures in surgical management of placenta accreta spectrum (PAS)—the modified one‐step conservative uterine surgery (MOSCUS), a new approach at Tu Du Hospital in Vietnam, versus cesarean hysterectomy, and to identify factors that appear to contribute to the successful outcome of the MOSCUS.MethodsThis retrospective study was conducted at Tu Du Hospital in southern Vietnam between January 2019 and December 2020. The study enrolled all pregnant women at more than 28 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…Similarly, Palacios-Jaraquemada et al indicated that lower PAS parametrial involvement is associated with severe hemorrhage and elevated maternal morbidity [ 44 ]. Also, a multidisciplinary team, the availability of blood banks, and ICUs are potentially necessary for cases who desire conservative uterine surgery [ 45 ]. In our study, we did not perform a cesarean hysterectomy in any of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Palacios-Jaraquemada et al indicated that lower PAS parametrial involvement is associated with severe hemorrhage and elevated maternal morbidity [ 44 ]. Also, a multidisciplinary team, the availability of blood banks, and ICUs are potentially necessary for cases who desire conservative uterine surgery [ 45 ]. In our study, we did not perform a cesarean hysterectomy in any of the cases.…”
Section: Discussionmentioning
confidence: 99%